Pyroptosis as a therapeutic target in preeclampsia: current research and future directions - Yongchun Zhu; Yuting Xiang; Yuting Xiang; Sathiskumar Swamiappan; Zhongjun Li; Zhongjun Li; Zhongjun Li; Xinsheng Peng (Frontiers in Immunology)
Preeclampsia (PE) is a severe pregnancy-specific disorder characterized by new-onset hypertension and proteinuria after the 20th week of gestation, posing significant threats to maternal and fetal health. Globally, approximately 4 million women are diagnosed with PE annually, resulting in over 70,000 maternal deaths and 500,000 infant deaths. The exact pathogenesis of PE remains unclear and is associated with multiple factors, including obesity, diabetes, and chronic kidney disease. Pyroptosis, a newly discovered form of programmed cell death, is characterized by plasma membrane rupture and the release of numerous inflammatory mediators. Studies have shown that trophoblast pyroptosis is closely related to PE, potentially hindering trophoblast invasion, causing abnormal remodeling of uterine spiral arteries, and inducing systemic inflammatory responses. This review summarizes the latest research progress on the correlation between trophoblast pyroptosis and the pathogenesis of PE. It explores the regulatory roles of NLRP3 Inflammasome,oxidative stress, T helper type 1 (Th1)/T helper type 2 (Th2) cell imbalance, microRNAs and other factors in trophoblast pyroptosis, providing potential targets for the development of early diagnostic biomarkers and therapeutic strategies for PE.